2013
DOI: 10.1016/j.jadohealth.2012.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Biological Contributions to Addictions in Adolescents and Adults: Prevention, Treatment, and Policy Implications

Abstract: Purpose Despite significant advances in our understanding of the biological bases of addictions, these disorders continue to represent a huge public health burden that is associated with substantial personal suffering. Efforts to target addictions require consideration of how the improved biological understanding of addictions may lead to improved prevention, treatment and policy initiatives. Method In this article, we provide a narrative review of current biological models for addictions with a goal of plac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
44
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 204 publications
(250 reference statements)
2
44
0
3
Order By: Relevance
“…Taken together, the differential relationship between different possible risk factors and problem-gambling severity highlights the importance of considering co-occurring conditions in understanding the health characteristics of adolescents with and without ARPG. Further research investigating the etiologies of these associations is needed to better inform prevention and other interventions efforts (Potenza 2013; Slavin et al 2013). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Taken together, the differential relationship between different possible risk factors and problem-gambling severity highlights the importance of considering co-occurring conditions in understanding the health characteristics of adolescents with and without ARPG. Further research investigating the etiologies of these associations is needed to better inform prevention and other interventions efforts (Potenza 2013; Slavin et al 2013). …”
Section: Discussionmentioning
confidence: 99%
“…Adolescence is an important developmental epoch characterized by elevated rates of impulsive and risk-seeking behaviors, making it a potentially vulnerable period for the development of addictions (Chambers et al 2003; Potenza 2013). Compulsive or problem shopping (PS) and problem/pathological gambling share many key clinical features of addictions (Hollander et al 2006; Potenza 2006; Grant et al 2011; Potenza 2013), and elevated rates of both have been reported among adolescents (Grant et al 2011; Villella et al 2011; Yip et al 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Impulsivity, whether measured by self-report, observer-report, or behavioral performance, is a robust predictor of current and future problems with substance use Jentsch & Taylor, 1999;Moeller et al, 2001;Moffitt et al, 2011;Nigg et al, 2006;Potenza, 2013;Tarter et al, 2003). In children, its association with future substance use remains even after controlling for other markers of risk, including low IQ, socioeconomic status, and parental history of substance dependence (Moffitt et al, 2011;Nigg et al, 2006;Tarter et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Variation in personality features such as impulsiveness, risk-taking and novelty seeking may contribute to the initiation of drug use as well to the progression to addiction [2]. It is well documented that reduced impulse control, or impulsivity is a characteristic feature of addiction [62,63] and is a premorbid marker of risk taking, with clear biological basis [64]. Several personality researchers have viewed impulsivity, sensation-seeking and risk taking as related personality traits [65][66][67].…”
Section: Discussionmentioning
confidence: 99%